Effect of adhesive remnant removal on enamel topography after bracket debonding - Larissa Adrian Meira Cardoso; Heloísa Cristina Valdrighi; Mario Vedovello Filho; Américo Bortolazzo Correr (Dental Press Editora, 2014)
INTRODUCTION: At orthodontic treatment completion, knowledge about the effects of adhesive remnant removal on enamel is paramount.OBJECTIVE: This study aimed at assessing the effect of different adhesive remnant removal methods on enamel topography (ESI) and surface roughness (Ra) after bracket debonding and polishing.METHODS: A total of 50 human premolars were selected and divided into five groups according to the method used for adhesive remnant removal: high speed tungsten carbide bur (TCB), Sof-Lex discs (SL), adhesive removing plier (PL), ultrasound (US) and Fiberglass burs (FB). Metal brackets were bonded with Transbond XT, stored at 37oC for 24 hours before debonding with adhesive removing plier. Subsequently, removal methods were carried out followed by polishing with pumice paste. Qualitative and quantitative analyses were conducted with pre-bonding, post-debonding and post-polishing analyses. Results were submitted to statistical analysis with F test (ANOVA) and Tukey's (Ra) as well as with Kruskal-Wallis and Bonferroni tests (ESI) (P < 0.05).RESULTS: US Ra and ESI were significantly greater than TCB, SL, PL and FB. Polishing minimized Ra and ESI in the SL and FB groups.CONCLUSION: Adhesive remnant removal with SL and FB associated with polishing are recommended due to causing little damage to the enamel.